Carta de Joaquín Martorell a Roberto H. Todd - Martorell, Joaquín; Todd, Roberto H. (My University, 1935)
Recuerdos de sus tiempos revolucionarios.
Keywords: Flags--Puerto Rico.; Bandera--Puerto Rico.